PERBAIKAN KUALITAS HASIL PRODUK KERAJINAN ALUMINIUM DI UD SARI REJEKI DESA BATUBULAN GIANYAR - ASTIKA, dkk., I MADE (Buletin Udayana Mengabdi; Vol 13 No 1 (2014): Vol 13, No 1, April 2014, 2014)
The existence of small industries in metal casting such as light decoration component is potential to develop. Because the process is still traditional and casting process based on experience of the workers, therefore there are some difficult parameters to be controlled such as melting temperature, pouring temperature and so on. Problems of the metal casting industry in ‘UD Sari Rejeki’ has very low quality and defective products. In order to solve those problems and improve product quality, the determent or election of melting and pouring temperature of metal castings can be undertaken. Implementation results show that the best product are obtained at 7500 C. At that temperature the best quality product was achieved. Keywords : casting, pouring temperature, melting temperature and quality